Combined in vitro IL-12 and IL-15 stimulation promotes cellular immune response in dogs with visceral leishmaniasis - Costa, Sidnei Ferro; Gomes, Vinícius Oliveira; dos Santos Maciel, Marilene Oliveira; Melo, Larissa Martins; Venturin, Gabriela Lovizutto; Bragato, Jaqueline Poleto; Rebech, Gabriela Torres; de Oliveira Santos, Catiule; Nascimento de Oliveira, Bárbara Maria; Gileno de Sá Oliveira, Geraldo; Felix de Lima, Valéria Marçal (PLOS Neglected Tropical Diseases, 2020)
Domestic dogs are the main reservoir of Leishmania infantum, a causative agent of visceral leishmaniasis (VL). The number of human disease cases is associated with the rate of canine infection. Currently available drugs are not efficient at treating canine leishmaniasis (CanL) and months after the treatment most dogs show disease relapse, therefore the development of new drugs or new therapeutic strategies should be sought. In CanL, dogs lack the ability to mount a specific cellular immune response suitable for combating the parasite and manipulation of cytokine signaling pathway has the potential to form part of effective immunotherapeutic methods. In this study, recombinant canine cytokines (rcaIL-12, rcaIL-2, rcaIL-15 and rcaIL-7) and soluble receptor IL-10R1 (rcasIL-10R1), with antagonistic activity, were evaluated for the first time in combination (rcaIL-12/rcaIL-2, rcaIL-12/rcaIL-15, rcaIL-12/rcasIL-10R1, rcaIL-15/rcaIL-7) or alone (rcasIL-10R1) to evaluate their immunomodulatory capacity in peripheral blood mononuclear cells (PBMCs) from dogs with leishmaniasis. All the combinations of recombinant proteins tested were shown to improve lymphoproliferative response. Further, the combinations rcaIL-12/rcaIL-2 and rcaIL-12/rcaIL-15 promoted a decrease in programmed cell death protein 1 (PD-1) expression in lymphocytes. These same combinations of cytokines and rcaIL-12/rcasIL-10R1 induced IFN-γ and TNF-α production in PBMCs. Furthermore, the combination IL-12/IL-15 led to an increased in T-bet expression in lymphocytes. These findings are encouraging and indicate the use of rcaIL-12 and rcaIL-15 in future in vivo studies aimed at achieving polarization of cellular immune responses in dogs with leishmaniasis, which may contribute to the development of an effective treatment against CanL.